2019
DOI: 10.1002/jmcd.12120
|View full text |Cite
|
Sign up to set email alerts
|

Counseling Canadian Indigenous Peoples: The Therapeutic Alliance and Outcome

Abstract: The aim of this study was to determine whether client therapeutic alliance ratings and client symptom severity were predictors of counseling outcomes among Canadian Indigenous clients. Participants included 179 Canadian Indigenous clients who completed an outcome measure at the 1st and last sessions and an alliance measure at both the 2nd and 3rd sessions. Results indicated that higher client alliance ratings at Sessions 2 and 3 and baseline client symptom severity were significant predictors of outcome. El ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 63 publications
2
14
0
Order By: Relevance
“…This measure asks patients to rate ten dimensions of therapeutic alliance (e.g., goal agreement, therapist understanding, patient feeling of acceptance) on a 5-point Likert scale with symmetrical anchors indicating a low (e.g., marking agree with this side for "I feel criticized or judged") or high (marking agree with this side for "I felt accepted") alliance. The 10-item SRS has been linked to clinical outcomes (Shaw et al, 2019) and influenced the development of the four-item SRS 3.0 (Duncan et al, 2003), which has been widely used (Murphy et al, 2020), with scores shown to relate to outcome in the context of psychotherapy (Sun et al, 2021). The community mental health setting preferred the 10-item version because it was determined to have more substantive process content to discuss with clients.…”
Section: Alliance Measuresmentioning
confidence: 99%
“…This measure asks patients to rate ten dimensions of therapeutic alliance (e.g., goal agreement, therapist understanding, patient feeling of acceptance) on a 5-point Likert scale with symmetrical anchors indicating a low (e.g., marking agree with this side for "I feel criticized or judged") or high (marking agree with this side for "I felt accepted") alliance. The 10-item SRS has been linked to clinical outcomes (Shaw et al, 2019) and influenced the development of the four-item SRS 3.0 (Duncan et al, 2003), which has been widely used (Murphy et al, 2020), with scores shown to relate to outcome in the context of psychotherapy (Sun et al, 2021). The community mental health setting preferred the 10-item version because it was determined to have more substantive process content to discuss with clients.…”
Section: Alliance Measuresmentioning
confidence: 99%
“…Recently, there has been renewed interest in indigenous counseling. Indigenous counseling emphasizes that culture is the main factor determining the formation of human behavior and counseling success (Fitriyah et al, 2022;Shaw et al, 2019;Wendt & Gone, 2016). In the fact, Islamic boarding schools is one of indigenous situation on Islamic culture.…”
Section: Introductionmentioning
confidence: 99%
“…The inherent belief in non-interference and collectivism can require mental health practitioners to consider a treatment approach that may stray from western approaches. Shaw et al (2019) stress the importance of noninterference as both a cultural feature and value that influences the therapeutic alliance between Indigenous clients and non-Indigenous mental health practitioners. In a study by Smith and Morrisette (2001), the need to establish strong therapeutic relationships was a central theme identified (as cited in Shaw et al, 2019).…”
Section: Trauma Informed Carementioning
confidence: 95%
“…In many settings, Indigenous peoples may underutilize mental health services because of lack of access, stigma, and mismatch with their needs and expectations (Gone & Kirmayer, 2020). Mainstream western conceptions of wellness and illness tend to focus on individualism and reductionism (Shaw et al, 2019). In contrast, Canadian Indigenous peoples view wellness as harmony amongst four dimensions of being: mental, physical, spiritual, and emotional (Shaw et al, 2019).…”
Section: Trauma Informed Carementioning
confidence: 99%
See 1 more Smart Citation